Studies of Some Physiological Traits on Spanish Goats Under Al-Gabal Al-Akhdar Conditions - El-Jarai, Ibrahim M.T.; Amaizik, Salem; Belkassem, Belkassem M. (Al-Mukhtar Journal of Sciences, 2008)
This experiment was carried out on 30 Spanish goats in different ages (1.5 month, 6-8 months, and ≤18 months) during winter season (12-150 C) to study some of blood constituents and skin characteristics and it's affected by age. Body weight was taken and selected blood parameters related to body metabolism were measured such as total protein, albumin, glucose, total cholesterol and urea nitrogen. Total globulin, albumin: globulin ratio were calculated. body temperatures, hair and skin temperatures and skin thickness of neck and flank were measured. Heat tolerance was calculated. Results indicated that a significant differences (P<0.0l) were obtained between ages in plasma total protein, where older animals were higher (13.77%) than younger animals. In contrast, younger animals were higher significantly (P<0.0l) in glucose percentage than older animals by about 32.29% and this is may be due to higher metabolism rate in younger animals compared by older animals. Results also, indicated that heat tolerance and skin thickness of neck and flank were increased significantly (P<0.0l) with increasing ages. In contrast, temperatures of body, hair, neck and flank were decreased significantly (P<0.0l) with increasing ages. The study showed that there was a significant (P<0.0l) negative correlation between age and body temperature (-0.78) and a significant (P<0.01) positive correlation between age and heat tolerance (+0.75), where there was a significant (P<0.0l) negative correlation between body temperature and heat tolerance (-0.96). It was concluded that age was more affect on some blood parameters and skin characteristics of Spanish goats and these changes in blood and skin parameters were showed that this breed successfully adapted under these conditions.